Efektivitas Kombinasi Terapi Komplementer Diaphragmatic Breathing dan Walking Exercise Terhadap Arus Puncak Ekspirasi Pasien PPOK - Laily Widya Astuti; Brilyan Anindya Dayfi (Jurnal Porkes, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a global health problem that causes a decline in lung function and quality of life. Pharmacological therapy alone is often insufficient to improve patients' functional capacity, while comprehensive pulmonary rehabilitation programs are difficult to access in primary health care. This study aims to evaluate the effectiveness of combining complementary diaphragmatic breathing therapy and walking exercise on improving peak expiratory flow (PEF) in stable COPD patients. The research method used a quasi-experimental pre-posttest design with a control group. A sample of 40 patients was divided into an intervention group (n=20) who received combination therapy for 2 weeks (6 sessions/week) and a control group (n=20) who only received standard therapy. PEF was measured using a peak flow meter before and after the intervention. The results showed a significant increase in PEF in the intervention group from 215.31 ± 16.72 to 301.52 ± 19.40 L/min (p=0.0001), while the control group only increased from 201.64 ± 12.14 to 221.62 ± 11.54 L/min. The increase in the intervention group was significantly greater than that in the control group (mean difference 66.23 L/min; p=0.0001). The study concluded that the combination of diaphragmatic breathing and walking exercise effectively improves lung function in COPD patients and can be used as a practical intervention in primary health care facilities.